Design standards for Muslim prayer facilities within public buildings - Mokhtar, Ahmed (2009)
The construction boom in the Arabian Gulf region has resulted in an inflow of consultants from around the world. Most have little or no experience of the particular requirements of the residents of the region, who are predominantly Muslim. One of these requirements is to have prayer facilities in public buildings to accommodate practicing Muslims who pray five times a day. The design requirements of such facilities are described only vaguely in commonly-used books on architecture design standards. The result is that inadequate design of such facilities in many projects causes discomfort to users. This paper describes an effort by an academic to support the profession with recommended standards for the design of prayer facilities. It covers not only the basic functional requirements of a prayer facility but also other issues such as fire protection and the relationship with supporting amenities such as ablution space. The research uses several methods to derive the recommended design standards. It draws from those few standards that already exist for the design standards of mosques and adapts them to prayer facilities within public buildings. It capitalizes on the author's experience as a space user who also has analytical capabilities in architecture design. Hence it studies well-designed spaces, identifies their strengths and incorporates them into the recommendations. It also studies poorly-designed spaces, identifies their weaknesses and recommends their avoidance. The purpose of the paper is to trigger more discussion on the design standards of such critical spaces in a region where there is a large population of users. The intention is to change the long-established practices of the many local and international consultants who design prayer facilities on an ad-hoc basis.